2012
DOI: 10.1534/genetics.111.134643
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Long Terminal Repeat Retrotransposon Genome Distribution in Natural Populations of the Wild Diploid WheatAegilops speltoides

Abstract: The environment can have a decisive influence on the structure of the genome, changing it in a certain direction. Therefore, the genomic distribution of environmentally sensitive transposable elements may vary measurably across a species area. In the present research, we aimed to detect and evaluate the level of LTR retrotransposon intraspecific variability in Aegilops speltoides (2n = 2x = 14), a wild cross-pollinated relative of cultivated wheat. The interretrotransposon amplified polymorphism (IRAP) protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Recently, we published the data from our long‐term study of the dynamics of TEs in natural populations of Ae. speltoides (Belyayev et al ., ; Hosid et al ., ). The results of the study showed that the TE fraction has undergone major changes in the genomes of plants from marginal populations.…”
Section: Genomic Explosion Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we published the data from our long‐term study of the dynamics of TEs in natural populations of Ae. speltoides (Belyayev et al ., ; Hosid et al ., ). The results of the study showed that the TE fraction has undergone major changes in the genomes of plants from marginal populations.…”
Section: Genomic Explosion Eventsmentioning
confidence: 99%
“…Indeed, our IRAP data on the intraspecific variability of LTR retrotransposons in Ae. speltoides show that various genotypes from the 13 populations studied differ significantly with respect to the patterns of the four explored LTR retrotransposons ( WIS2, Wilma, Daniela and Fatima ) (Hosid et al ., ).…”
Section: Nursery For Biodiversitymentioning
confidence: 99%
“…speltoides possesses a wide spectrum of chromosomal rearrangements and extranumerary B chromosomes [Mendelson and Zohary, 1972;Raskina et al, 2004aRaskina et al, , b, 2011 which are highly enriched with nuclear repetitive and organelle DNA [Ruban et al, 2014]. According to the chromosomal patterns of tandem repeats [Raskina et al, 2011] and inter-retrotransposon amplified polymorphism [Hosid et al, 2012], wild populations can be clustered into 3 groups, which reflect the Ae. speltoides ecogeographical gradient and highlight the impact of repetitive DNA on population divergence and evolutionarily significant events that lead to speciation at the diploid level and via allopolyploidy [Raskina et al, 2004a[Raskina et al, , b, 2008.…”
mentioning
confidence: 99%
“…It has been proven that TE families evolve with different profiles, so TE marker systems based on different TEs show different levels of resolution and can be chosen to fit with the required analysis (Leigh et al, 2003;Smykal et al, 2009;Hosid et al, 2012). Retrotranspo sons insertions behave as Mendelian loci (Manninen et al, 2006;Tanhuanpaa et al, 2008).…”
Section: Retrotransposon-based Marker Systemsmentioning
confidence: 99%
“…IRAP and REMAP methods have been used in gene map ping in cereals (Manninen et al, 2000;Boyko et al, 2002;Tanhuanpaa et al, 2007), in studies of genome evolution in the Solanaceous crop species (Tek et al, 2005;Tam et al, 2009), in a variety of applications, including measurement of genetic diversity and population structure, chromatin modification and epigenetic reprogramming, similarity and cladistic relation ships, determination of essential derivation, markerassisted selection, detection of somaclonal variation (Ishizaki, Kato, 2005;Lightbourn et al, 2007;Tam et al, 2009;Belyayev et al, 2010;Smykal et al, 2011;Wenke et al, 2011;Hosid et al, 2012;Yin et al, 2013;Moisy et al, 2014;Sharma, Nandineni, 2014;Tang et al, 2014;Paz et al, 2015).…”
Section: Retrotransposon-based Marker Systemsmentioning
confidence: 99%